2016
DOI: 10.1161/strokeaha.115.010613
|View full text |Cite|
|
Sign up to set email alerts
|

Missed Ischemic Stroke Diagnosis in the Emergency Department by Emergency Medicine and Neurology Services

Abstract: A retrospective chart review was performed on all patients with a discharge diagnosis of ischemic stroke during a 1-year period from Background and Purpose-The failure to recognize an ischemic stroke in the emergency department is a missed opportunity for acute interventions and for prompt treatment with secondary prevention therapy. Our study examined the diagnosis of acute ischemic stroke in the emergency department of an academic teaching hospital and a large community hospital. Methods-A retrospective char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
110
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(122 citation statements)
references
References 20 publications
7
110
0
5
Order By: Relevance
“…6 In a 2016 US single hospital retrospective chart review, 20% of strokes were initially 'missed' although these data have limited generalisability to an entire healthcare system such as the NHS in the UK. 7 If the diagnosis of acute stroke continues to go unrecognised in patients who are initially admitted to general admissions units, the opportunity for secondary prevention can be lost. These patients can have delayed access to stroke unit care, which conveys an increased likelihood of being…”
Section: Mimics and Chameleons In Strokementioning
confidence: 99%
See 2 more Smart Citations
“…6 In a 2016 US single hospital retrospective chart review, 20% of strokes were initially 'missed' although these data have limited generalisability to an entire healthcare system such as the NHS in the UK. 7 If the diagnosis of acute stroke continues to go unrecognised in patients who are initially admitted to general admissions units, the opportunity for secondary prevention can be lost. These patients can have delayed access to stroke unit care, which conveys an increased likelihood of being…”
Section: Mimics and Chameleons In Strokementioning
confidence: 99%
“…8 It has been suggested that this group has higher rates of readmission at 60 days and disability and mortality at 12 months. 7,9 Stroke mimics Seizure, syncope, sepsis, migraine, space-occupying lesions, functional disorders and metabolic conditions are the seven most frequent differential diagnoses of suspected stroke. 10 Computerised tomography (CT) imaging can identify some space-occupying lesions and hypoglycaemia is detectable with bedside glucose monitoring.…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Misdiagnosis of acute stroke may result in worse patient functional outcomes due to failure to implement acute stroke interventions as well as standard processes of care [6]. Studies have reported that 2-26% of acute stroke presentations are misdiagnosed in the emergency department (ED) [5,[7][8][9][10]. Factors contributing to stroke misdiagnosis include non-specific or atypical symptoms [5,10], such as those associated with posterior circulation stroke (PCS) [8,10,11], decreased level of consciousness [9], younger patient age [8,9,12], lower cerebrovascular disease profile [8], and transient ischemic attack (TIA) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Posterior circulation strokes are misdiagnosed 3 times more frequently than anterior circulation strokes [8] . Younger patient age [4,9] , nausea and or vomiting [8] , dizziness [8] , vertebral artery dissection [4] and prior history of stroke [8] are all associated with misdiagnosis of posterior circulation strokes. CBI most frequently involves the posterior inferior cerebellar arterial (PICA) territory but reported outcomes according to vascular territory involvement are inconsistent [4,6,10] .…”
Section: Introductionmentioning
confidence: 99%